Philippines : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues paper reports that the Philippines is influenced by global developments through both trade and financial channels. Weaker global growth hurts demand for Philippine exports, which in turn affects consumption and investment. The financial system has only limited exposure to Europe and little reliance on foreign wholesale funding, but contagion could still occur through pullbacks of credit by European banks to the domestic corporate sector or a retreat by foreign investors from local equity and bond markets.